2004
DOI: 10.1111/j.1365-2966.2004.08150.x
|View full text |Cite
|
Sign up to set email alerts
|

Three new X-ray pulsars detected in the Small Magellanic Cloud and the positions of two other known pulsars determined

Abstract: Three new X‐ray pulsars have been detected in the Small Magellanic Cloud (SMC) and the positions of two others have been determined, with archive Chandra data. A series of five observations of the SMC took place between 2002 May and October. Analysis of these data has revealed three previously unknown X‐ray pulsars at pulse periods of 34, 503 and 138 s. The position of pulsar XTE J0052−725, which was originally detected by RXTE on 2002 June 19, was also accurately determined and a previously detected 7.78‐s RX… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 21 publications
2
41
0
Order By: Relevance
“…This field is located in the central bar region, north of field 404680201 with a small overlap. In the EPIC images of this observation we detected the three known Be/X-ray binary pulsars SMC X-3 (7.79 s; Edge et al 2004a), CXOU J005323.8-722715 (138 s; Edge et al 2004b) and XTE J0055-724 (=1SAX J0054.9-7226 =1WGA J0054.9-7226 = RX J0054.9-7226, 59 s; . Galache et al (2008).…”
Section: Observations and Data Analysismentioning
confidence: 84%
See 1 more Smart Citation
“…This field is located in the central bar region, north of field 404680201 with a small overlap. In the EPIC images of this observation we detected the three known Be/X-ray binary pulsars SMC X-3 (7.79 s; Edge et al 2004a), CXOU J005323.8-722715 (138 s; Edge et al 2004b) and XTE J0055-724 (=1SAX J0054.9-7226 =1WGA J0054.9-7226 = RX J0054.9-7226, 59 s; . Galache et al (2008).…”
Section: Observations and Data Analysismentioning
confidence: 84%
“…This pulsar was discovered in a Chandra observation on 2002 July 20 (Edge et al 2004b) with a period of 138.04±0.61 s (98% confidence). We confirm this source as a pulsar and determined the period to be 139.136±0.016 s from the XMM-Newton observation on 2007 June 23, indicating significant spin-down of the neutron star.…”
Section: The 172 S Be/x-ray Binary Pulsar Ax J00516-7311mentioning
confidence: 92%
“…Despite of the early proposed optical identification (van Paradijs et al 1977;Crampton et al 1978) the nature of the source remained uncertain for a long time. Only in 2004, Edge et al (2004) using the Chandra data had shown that the 7.78 s pulsar found by Corbet et al (2004) in the RXTE data can be identified with A&A proofs: manuscript no. smcx3_aa SMC X-3.…”
Section: Introductionmentioning
confidence: 97%
“…smcx3_aa SMC X-3. Based on the precise X-ray position reported by Edge et al (2004), Cowley & Schmidtke (2004) studied the long term optical light curve of SMC X-3 and established its counterpart as a O9e star. A number of outbursts detected with the RXTE observatory in 1999-2009 allowed to find a periodicity in the source activity, likely associated with the orbital motion with the period of ≃ 45 days (Corbet et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The large X-ray flux variation in the long time span, the flat powerlaw spectrum and the existence of emission lines strongly favor that AX J0051-733 is a Be/X-ray binary (Imanishi et al, 1999;Coe et al, 2002;Edge et al, 2004). From its position at the P 0 − P s diagram, a safe lower limit of the initial magnetic field strength of 4.2 × 10 13 G can be inferred, by assuming that the Be star has polar wind only.…”
Section: Discussionmentioning
confidence: 96%